2012
DOI: 10.1007/s00436-011-2800-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes in mice caused by Toxoplasma gondii invasion of brain

Abstract: Toxoplasma gondii, a protozoan parasite, is capable of infecting a broad range of intermediate warm-blooded hosts including humans. The parasite undergoes sexual reproduction resulting in genetic variability only in the intestine of the definitive host (a member of the cat family). The parasite seems to be capable of altering the natural behavior of the host to favor its transmission in the environment. The aim of this study was to evaluate the number of parasite cysts formed in the hippocampus and amygdala of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 29 publications
6
57
0
1
Order By: Relevance
“…Furthermore, real-time PCR was used to determine the expression of SAG1, BAG1, and GRA1 in the brain tissues and showed that neither the expression of the bradyzoite marker nor the low level of expression of SAG1 was specific to any particular brain region, suggesting that there was no cyst tropism. Consistent with the findings of previous studies in mice, T. gondii had no obvious preference for specific brain regions (12)(13)(14). In addition, no other study has reported clear evidence to support the idea that parasite localization plays a critical role in the behavioral changes induced by T. gondii infection (9,15,16,43).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, real-time PCR was used to determine the expression of SAG1, BAG1, and GRA1 in the brain tissues and showed that neither the expression of the bradyzoite marker nor the low level of expression of SAG1 was specific to any particular brain region, suggesting that there was no cyst tropism. Consistent with the findings of previous studies in mice, T. gondii had no obvious preference for specific brain regions (12)(13)(14). In addition, no other study has reported clear evidence to support the idea that parasite localization plays a critical role in the behavioral changes induced by T. gondii infection (9,15,16,43).…”
Section: Discussionsupporting
confidence: 88%
“…First, the relationship between parasite localization in the brain and behavioral changes has been investigated, with a previous study reporting that T. gondii has no obvious tropism in the brain (12)(13)(14)(15). However, another study found that tissue cyst density in amygdalar areas (the medial and basolateral amygdala) is 2-fold higher than that in nonamygdalar areas (9), whereas the presence of tissue cysts in the forebrain contributes to the attenuation of predator odor aversion and anxiety-like behavior (16).…”
mentioning
confidence: 99%
“…Hence, it is essential to prove that the strain used in this study, Pru⌬ku80⌬hxg, induces an increase in dopamine prior to gene knockout studies. An increase in dopamine in brains of infected mice was also not reproduced as in previously published studies (3)(4)(5). Furthermore, Wang et al used a different outbred mouse line for their in vivo study than that reported by Prandovszky at al.…”
mentioning
confidence: 80%
“…Prior work has found altered dopamine neurotransmission with T. gondii infection (2)(3)(4)(5). In the study of Wang et al, dopaminergic PC12 cell cultures were incubated at alkaline pH to examine dopamine levels in bradyzoite-infected cells, a standard procedure used to induce parasite conversion in fibroblasts, yet the synthesis of dopamine in PC12 cells is sensitive to pH changes (6).…”
mentioning
confidence: 99%
“…Few studies have also described impaired sensorimotor functions, which manifested in the form of poor performance in grip strength and balance beam tests, diminished exploratory activity and gait alterations, but involvement of the spinal cord was not addressed [31,32]. All together, these observations suggest that spinal cord pathology should receive increased attention similar to brain pathology, to further elucidate the behavioral changes in mice caused by T. gondii infection.…”
Section: Introductionmentioning
confidence: 99%